Formulasi Nanoemulgel Minyak Cendana-Aloe Vera Berbasis Gelling Agent Derivat Selulosa: Studi Karakteristik Dan Stabilitas - Dita Nurlita Rakhma; Nanda Aprilia; Yuyun Nailufa; Yuli Ainun Najih (Poltekkes Kemenkes Bengkulu, 2026)
Sandalwood oil possesses anti-inflammatory potential for sunburn management; however, its volatility and low water solubility limit topical effectiveness. Aloe vera is widely known for its effectiveness as a skin moisturizer and anti-inflammatory. The combination of sandalwood oil and aloe vera in a nanoemulgel-based topical formulation has great potential for development. Nanoemulgel systems may enhance stability and skin delivery, while the type of gelling agent critically influences physical characteristics and stability. This study aimed to evaluate the effect of different gelling agents on the physical characteristics and stability of sandalwood oil-aloe vera nanoemulgel. Methods: Three nanoemulgel formulations were prepared using different cellulose derivative gelling agents (MC, HPMC, and HEC). Physical evaluations included organoleptic assessment, pH, viscosity, spreadability, adhesiveness, particle size, polydispersity index (PDI), and centrifugation stability testing. Data were analyzed using one-way ANOVA (p<0.05). All formulations showed acceptable pH and homogeneous nano-sized droplets (30–50 nm) with PDI <0.35. Significant differences were observed in viscosity and particle size (p<0.05). The HEC-based formulation exhibited the highest viscosity and the smallest particle size. Increased viscosity was associated with reduced droplet mobility and improved physical stability. Spreadability showed an inverse relationship with viscosity, while adhesiveness was not significantly different among formulations. All formulations remained physically stable without phase separation after centrifugation. The type of gelling agent significantly affected the physical characteristics of nanoemulgel, and the HEC-based formulation demonstrated the most optimal performance in characteristics and physical stability.